Cold-resistant and tear-resistant coating resin and preparation method thereof
By forming a synergistic reinforcing network between modified epoxy resin and nano-silica, the problem of embrittlement and cracking of coating resin at low temperatures is solved, achieving stability and tear resistance in low-temperature environments, and improving the performance and ease of application of the coating.
Patent Information
- Application Number
- CN202511479446.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-10-16
- Publication Date
- 2025-12-02
AI Technical Summary
Existing coating resins are prone to embrittlement and cracking at low temperatures, have poor tear resistance, and are unstable in preparation, making it difficult to meet the requirements of performance consistency and ease of construction in industrial applications.
A synergistic reinforcing network is formed by modifying epoxy resin and modified nano-silica. The resin's flexibility and mechanical strength are improved through three modification treatments. A specific solvent system is used to ensure uniform mixing and stable dispersion, control the moisture content, and optimize the preparation process parameters.
It maintains the stability and tear resistance of the coating in low-temperature environments, improves the mechanical properties and ease of application of the coating, extends the protective life of the substrate, and maintains good weather resistance and adhesion in complex environments.
Abstract
Description
Technical Field
[0001] This invention relates to the field of coating technology, specifically to a cold-resistant and tear-resistant coating resin and its preparation method. Background Technology
[0002] In the field of coating technology, substrates used in low-temperature environments, such as outdoor pipes, vehicle parts, and flexible packaging materials, are facing increasingly stringent requirements for the cold resistance and tear resistance of coatings. Existing coating resins mostly rely on single resin systems, which, although possessing certain mechanical properties, are prone to embrittlement and cracking in low-temperature environments below -20°C, resulting in a significant decrease in tear strength and making it difficult to meet long-term use requirements.
[0003] Some improvement solutions attempt to add plasticizers to improve cold resistance, but this can easily lead to a decrease in coating hardness and a deterioration in weather resistance. Other technologies introduce nanoparticles to enhance tear resistance, but because nanoparticles have poor compatibility with resin and are prone to agglomeration, they cannot fully exert their reinforcing effect and may also cause surface defects in the coating.
[0004] Meanwhile, in existing preparation processes, improper control of raw material moisture content often leads to side reactions between key raw materials such as diphenylmethane diisocyanate and water, generating bubbles and gels, damaging the resin cross-linking network, and further reducing the stability of coating performance. Furthermore, most coating preparation process parameters are vague, have poor repeatability, and are difficult to scale up for production, failing to meet the requirements of consistent coating performance and ease of application in industrial applications. Therefore, there is an urgent need to develop a coating resin that combines excellent cold resistance and tear resistance with stable preparation and good workability. Summary of the Invention
[0005] To address the shortcomings of existing technologies, this invention provides a cold-resistant and tear-resistant coating resin and its preparation method, solving the problems of low-temperature brittleness, poor tear resistance, and unstable preparation of traditional coating resins.
[0006] To achieve the above objectives, the present invention provides the following technical solution: A cold-resistant and tear-resistant coating resin comprises the following raw materials in parts by weight: 40-60 parts modified epoxy resin, 15-25 parts polyhexane adipate diol, 5-10 parts modified nano silica, 8-15 parts diphenylmethane diisocyanate, 3-8 parts trimethylolpropane, 10-20 parts methyl methacrylate, 8-15 parts butyl acrylate, 0.5-2 parts benzoyl peroxide, 0.2-0.8 parts dibutyltin dilaurate, 1-3 parts silane coupling agent KH-550, 0.3-1 part antioxidant 264, 5-12 parts dioctyl phthalate, and 20-35 parts mixed organic solvent.
[0007] Furthermore, the mixed organic solvent is composed of methyl ethyl ketone (MEK), butyl acetate, and xylene in a ratio of 3:4:3. Through the synergistic effect of these three components, it exhibits excellent solubility and dispersibility for modified epoxy resin, polyurethane prepolymer, acrylate copolymer, and modified nano-silica. This avoids system stratification or precipitation caused by insufficient solubility of a single solvent, ensuring uniform mixing of all raw materials to form a stable coating system.
[0008] Furthermore, the modified epoxy resin is prepared using the following specific steps: A1. Add bisphenol A type epoxy resin to a dry four-necked flask, add epichlorohydrin, stir and heat to 60-70℃, slowly add 30% sodium hydroxide solution dropwise over 1.5-2 hours, and keep the reaction at 70-80℃ for 3-4 hours; after the reaction, add polyethylene glycol with a molecular weight of 1000, heat to 90-100℃, add boron trifluoride diethyl ether complex, and stir for 4-5 hours; then cool to 50-60℃, wash 2-3 times with anhydrous ethanol, and remove ethanol and epichlorohydrin by vacuum distillation at 80℃ and -0.095MPa to obtain the first modified epoxy resin; A2. Take the first modified epoxy resin and add it to a dry four-necked flask. Add xylene, stir and heat to 80-90℃, then slowly add maleic anhydride and hydroquinone, heat to 110-120℃ and keep the temperature for 5-6 hours. Then cool down to 80-90℃, add silane coupling agent KH-560 and dibutyltin dilaurate, stir and react for 3-4 hours, and then remove xylene by vacuum distillation at 100℃ and -0.09MPa to obtain the second modified epoxy resin. A3. Take the second modified epoxy resin and add it to a dry four-necked flask. Add N,N-dimethylformamide, stir and heat to 70-80℃, then add nano-calcium carbonate treated with silane coupling agent KH-550, and ultrasonically disperse for 30-40 minutes. Then add benzoyl peroxide, heat to 90-100℃ and stir to react for 4-5 hours. After the reaction is completed, cool to room temperature, filter, and obtain the modified epoxy resin.
[0009] Furthermore, the nano-calcium carbonate in A3 treated with silane coupling agent KH-550 is specifically treated as follows: 100g of nano-calcium carbonate is vacuum dried at 120℃ for 4h, 150ml of anhydrous ethanol is added and ultrasonically dispersed for 30min, then 10ml of silane coupling agent KH-550 is added, the pH is adjusted to 5 with anhydrous acetic acid, and the reaction is stirred at 60℃ and 500r / min for 3h. After the reaction is completed, the reaction solution is centrifuged, the precipitate is washed 3 times with anhydrous ethanol, and vacuum dried at 90℃ for 5h. Vacuum drying at 120℃ for 4 hours removes adsorbed water from the surface of nano-calcium carbonate, preventing moisture from affecting subsequent reactions. Ultrasonic dispersion for 30 minutes breaks up particle aggregation, creating a uniform surface for coupling agent grafting. Silane coupling agent KH-550, under anhydrous acetic acid-adjusted pH=5 conditions, reacts more efficiently with the hydroxyl groups on the surface of nano-calcium carbonate to form an organic coating layer, improving its compatibility with the resin. Stirring at 60℃ and 500 r / min ensures sufficient coupling agent grafting. Vacuum drying at 90℃ for 5 hours fixes the modification effect, ultimately yielding modified nano-calcium carbonate with good dispersibility and high resin compatibility, preventing aggregation in epoxy resin and fully leveraging its reinforcing effect.
[0010] Furthermore, the ratio of bisphenol A type epoxy resin, epichlorohydrin, sodium hydroxide solution, polyethylene glycol, and boron trifluoride diethyl ether complex in A1 is 400-500g: 120-150ml: 80-100ml: 80-100g: 0.2-0.5g.
[0011] Furthermore, the ratio of the first modified epoxy resin, xylene, maleic anhydride, hydroquinone, silane coupling agent KH-560, and dibutyltin dilaurate in A2 is 300-400g: 100-120ml: 60-80g: 1-2g: 50-70g: 0.2-0.5g.
[0012] Furthermore, the ratio of the second modified epoxy resin, N,N-dimethylformamide, nano-calcium carbonate treated with silane coupling agent KH-550, and benzoyl peroxide in A3 is 200-300g: 80-100ml: 30-50g: 5-8g.
[0013] In A1, bisphenol A type epoxy resin is used as the base material. First, the epoxy group density is adjusted through a ring-opening-ring-closing reaction of epichlorohydrin and sodium hydroxide. Then, polyethylene glycol with a molecular weight of 1000 is added. Under the catalysis of boron trifluoride diethyl ether complex, the hydroxyl groups of polyethylene glycol undergo an etherification reaction with the epoxy groups of the epoxy resin, grafting flexible polyether segments onto the epoxy resin molecular backbone. These segments can move freely at low temperatures, alleviating the embrittlement problem caused by rigid molecular chain aggregation. Simultaneously, it avoids the problems of insufficient flexibility due to excessively small molecular weight or hindered cross-linking caused by excessively large molecular weight, laying the foundation for the resin's cold resistance.
[0014] In A2, the first modified product reacts with maleic anhydride, introducing active groups such as carboxyl and ester groups into the molecular chain to enhance its reactivity with subsequent modified components. Hydroquinone acts as a polymerization inhibitor to prevent the self-polymerization of maleic anhydride from affecting the reaction efficiency. Subsequently, the silane coupling agent KH-560 is added, whose epoxy groups undergo esterification with the carboxyl groups of the resin, grafting organosilicon segments onto the molecular chain. The organosilicon segments have low surface energy and excellent weather resistance, which can improve the interfacial bonding between the resin and the substrate and nanoparticles, while enhancing the coating's resistance to ultraviolet aging and preventing performance degradation after long-term use.
[0015] A3 is added with nano-calcium carbonate treated with silane coupling agent KH-550. Through ultrasonic dispersion and reaction initiated by benzoyl peroxide, the nano-calcium carbonate is grafted onto the resin molecular chain. The nano-reinforcing effect is used to improve the mechanical strength of the resin. The filtration step removes unreacted impurities, and finally a modified epoxy resin with flexibility, weather resistance and high strength is obtained, which provides the core support for the coating's cold resistance and tear resistance.
[0016] Furthermore, the modified nano-silica is prepared using the following specific steps: B1. Add nano-silica to anhydrous ethanol, sonicate for 20-30 min, then add silane coupling agent KH-550, adjust pH to 4-5 with anhydrous acetic acid, stir and react at 50-60℃ for 3-4 h; after the reaction, centrifuge, wash 3 times with anhydrous ethanol, and vacuum dry at 80-100℃ for 4-5 h to obtain the first modified nano-silica. B2. Add the first-modified nano-silica to a dry four-necked flask, add anhydrous toluene, and ultrasonically disperse for 30-40 min. Then add dehydrated sorbitol monooleate and stir for 30 min. Next, add a mixture of methyl methacrylate and butyl acrylate monomers dropwise. Heat to 70-80℃, add azobisisobutyronitrile, and keep the reaction at this temperature for 4-5 h. After the reaction is completed, cool to room temperature, centrifuge, wash three times with anhydrous ethanol, and vacuum dry at 80-100℃ for 5-6 h to obtain the second-modified nano-silica. B3. Take the second batch of modified nano-silica and add it to a dry four-necked flask. Add toluene, stir and heat to 80-90℃, add isocyanate propyltriethoxysilane and dibutyltin dilaurate, and stir to react for 3-4 hours. After the reaction is completed, cool down to 60-70℃, add 50% solid content hydroxyl acrylic resin, stir to react for 2-3 hours, and then remove toluene by vacuum distillation at 90℃ and -0.09MPa to obtain modified nano-silica.
[0017] Furthermore, the ratio of nano-silica, anhydrous ethanol, and silane coupling agent KH-550 in B1 is 100-150g: 200-250ml: 15-20ml.
[0018] Furthermore, the ratio of the first modified nano-silica, anhydrous toluene, dehydrated sorbitol monooleate, methyl methacrylate, butyl acrylate, and azobisisobutyronitrile in B2 is 80-100g: 150-200ml: 2-3g: 30-40ml: 20-30ml: 1-2g.
[0019] Furthermore, the ratio of the amount of the second modified nano-silica, toluene, propyltriethoxysilane isocyanate, dibutyltin dilaurate, and hydroxyl acrylic resin in B3 is 60-80g: 120-150ml: 10-15g: 0.1-0.3g: 8-12g.
[0020] The nano-silica in B1 is rich in hydroxyl groups on its surface, making it prone to aggregation and exhibiting poor compatibility with organic resins. After uniformly dispersing it in anhydrous ethanol using ultrasonic dispersion, a silane coupling agent, KH-550, was added. Under an acidic environment of pH 4-5, the siloxane bonds of the silane coupling agent KH-550 hydrolyzed to generate silanol groups, which then condensed with the hydroxyl groups on the nano-silica surface to form stable Si-O-Si bonds, grafting amino and other organic functional groups onto the nano-silica surface. The modified nano-silica surface changed from hydrophilic to hydrophobic, preventing aggregation in organic resins and laying the interfacial foundation for further modification.
[0021] In anhydrous toluene, B2 dehydrated sorbitol monooleate adsorbs onto the surface of the first-modified nano-silica, further optimizing its dispersibility. Subsequently, a mixture of methyl methacrylate and butyl acrylate monomers is added dropwise. Under the initiation of azobisisobutyronitrile (AIBN), the mixed monomers undergo free radical polymerization on the nano-silica surface, forming an acrylate polymer coating layer. The structure of this coating layer is highly matched with the acrylate segments in the coating resin, which can enhance the bonding force between the nano-silica and the resin matrix through intermolecular forces, preventing particles from detaching from the resin matrix under stress and ensuring the reinforcing effect.
[0022] In B3, isocyanate propyltriethoxysilane is added. Its isocyanate groups react with the residual hydroxyl and amino groups on the surface of nano-silica, while the siloxane bonds further cross-link and solidify, improving the stability of the coating layer. Then, hydroxyl acrylic resin is added, and its hydroxyl groups undergo a urethane reaction with the isocyanate groups, grafting hydroxyl acrylic resin segments onto the surface of nano-silica. Ultimately, the modified nano-silica not only enhances the mechanical properties of the coating through physical filling but also participates in the construction of the overall cross-linking network of the resin through chemical cross-linking, forming a "synergistic reinforcing network" with the modified epoxy resin, simultaneously improving the coating's tear resistance and structural stability.
[0023] A method for preparing a cold-resistant and tear-resistant coating resin specifically includes the following steps: S1. Add the mixed organic solvent to the dry stirring tank, then add dibutyltin dilaurate, silane coupling agent KH-550 and antioxidant 264 in sequence, stir at 300-500 r / min for 15-20 min to obtain the premixed solution. The whole process is under nitrogen protection to avoid oxidation of raw materials and provide a stable basic system for subsequent reactions. S2. Slowly add modified epoxy resin and polyhexanediol adipate to the premix, stir at 600-800 r / min for 30-40 min, then add modified nano silica to the mixture while stirring, ultrasonically disperse at 300-500 W for 40-60 min and keep stirring at 500-600 r / min to make the nanoparticles uniformly dispersed in the resin system and give full play to the reinforcing effect. S3. Under nitrogen protection, heat the mixed system to 60-70℃, slowly add diphenylmethane diisocyanate dropwise over 1-1.5 hours, stirring at 700-900 r / min. After the addition is complete, keep the mixture at 70-80℃ for 2-3 hours to ensure a full cross-linking reaction and the formation of a stable cross-linked network. S4. Cool the system to 50-60℃, add trimethylolpropane, and stir for 15-20 minutes; slowly add a mixture of methyl methacrylate, butyl acrylate and benzoyl peroxide, and add it dropwise over 1-1.5 hours. Simultaneously raise the temperature to 80-90℃ and keep it at that temperature for 3-4 hours to ensure complete copolymerization and form acrylate segments that have both hardness and flexibility. S5. Cool the system to 40-50℃, add dioctyl phthalate, and stir for 20-30 minutes; use a Fork-4 cup at 25℃ to test the viscosity and control it within 15-30 seconds; filter the coating through a 100-200 mesh dry nylon filter to avoid defects such as pinholes and particles on the coating surface, and obtain a cold-resistant and tear-resistant coating resin.
[0024] Furthermore, all raw materials involved in the entire process of preparing modified epoxy resin, modified nano-silica, and coating resin must be dried and dehydrated before being added to the reaction. The moisture content of the raw materials after treatment must be controlled below 0.1%, and the equipment used in the reaction must be dried beforehand to ensure the entire reaction system is in a low-water or anhydrous environment. The core reactions of the system, the polyurethane prepolymerization reaction of diphenylmethane diisocyanate and hydroxyl groups, and the epoxy resin crosslinking reaction, are extremely sensitive to moisture. Moisture preferentially reacts with diphenylmethane diisocyanate to generate urea bonds and carbon dioxide, leading to foaming and gelation of the system, while simultaneously consuming epoxy groups in the epoxy resin and destroying the crosslinking network. Moisture on the surface of nanoparticles hinders the grafting of modifiers such as silane coupling agents, causing particle aggregation and loss of reinforcing effect. Moisture in monomers and solvents reduces the decomposition efficiency of oil-soluble initiators, leading to incomplete polymerization and residual monomers causing coating defects. Moisture in additives also reduces catalyst activity and accelerates the degradation of antioxidants, ultimately resulting in abnormal resin structure and a significant decrease in the mechanical properties and stability of the coating.
[0025] This invention provides a cold-resistant and tear-resistant coating resin and its preparation method, which has the following beneficial effects: 1. This invention modifies epoxy resin in three stages: first, polyethylene glycol segments are introduced to improve resin flexibility; then, organosilicon chains are grafted to enhance weather resistance; and finally, nano-calcium carbonate is grafted to improve mechanical strength. Simultaneously, nano-silica undergoes silane coupling modification, acrylate coating, and hydroxyl acrylic resin grafting, forming a synergistic reinforcing network between the modified epoxy resin and the modified nano-silica in the system. These two components, along with polyhexamethylene adipate diol and diphenylmethane diisocyanate to form polyurethane segments, retain the high strength characteristics of epoxy resin while effectively solving the problem of traditional coatings becoming brittle and cracking at low temperatures through the dispersion and reinforcement effects of polyether chains, organosilicon chains, and nanoparticles. This significantly improves the coating's tear resistance, ensuring stable mechanical properties even at temperatures below -20°C and in scenarios with repeated deformation, thus extending the substrate's protective lifespan.
[0026] 2. This invention explicitly requires that all raw materials in the entire process of preparing modified epoxy resin, modified nano-silica, and coating resin must be dried and dehydrated to a moisture content of less than 0.1%, and the reaction equipment must be pre-dried. This design avoids, from the outset, the formation of urea bonds and carbon dioxide from the reaction of water with diphenylmethane diisocyanate, which would lead to foaming and gelation of the system. It also prevents the reaction of water with the epoxy groups of epoxy resin from damaging the cross-linking network and hindering the grafting of nanoparticles with the modifier. Simultaneously, the raw material ratios and reaction parameters in each step are precisely defined to ensure consistent resin cross-linking density and nanoparticle dispersion in each batch of product, avoiding coating performance instability caused by fluctuations in raw material moisture content or deviations in process parameters, thus improving product quality reliability.
[0027] 3. This invention uses a mixed organic solvent composed of methyl ethyl ketone (MEK), butyl acetate, and xylene in a 3:4:3 ratio as the dispersion medium. This solvent system exhibits good solubility and dispersibility for modified epoxy resin, polyurethane prepolymer, acrylate copolymer, and modified nano-silica, allowing for uniform mixing of the components to form a stable coating system. Simultaneously, by controlling the amount of dioctyl phthalate added during the preparation process and adjusting the viscosity with the mixed organic solvent to 15-30 seconds at 25°C using a Ford cup (Cup 4), the coating achieves suitable application fluidity, meeting the requirements of various application methods such as brushing and spraying. This avoids coating sagging due to excessive viscosity or uneven film thickness due to insufficient viscosity. Furthermore, filtering the coating through a 100-200 mesh dry nylon filter removes incompletely dispersed particles or impurities, reducing pinholes and particle defects on the coating surface after film formation, thus improving coating density and surface smoothness.
[0028] 4. The antioxidant 264 introduced in the formulation of this invention can effectively inhibit the degradation of resin chains caused by oxidation and light exposure during long-term use, delaying the aging and yellowing of the coating and the decline in mechanical properties. The silane coupling agent KH-550 not only enhances the interfacial bonding force between the modified nano-silica and the resin matrix, but also strengthens the adhesion between the coating and substrates such as metals, plastics, and wood, preventing the coating from peeling off under thermal cycling or external forces. At the same time, the modified resin system combines the weather resistance of organosilicon chains with the chemical corrosion resistance of polyurethane chains, enabling the coating to maintain good cold resistance, tear resistance, and appearance integrity under complex conditions such as outdoor sun and rain exposure and industrial acid and alkali corrosion, thus broadening the application scenarios of the coating. Detailed Implementation
[0029] The technical solutions in the embodiments of the present invention will be clearly and completely described below. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.
[0030] All substances used in the following examples and comparative examples have been dried and have a moisture content of less than 0.1%.
[0031] Example 1: Preparation of cold-resistant and tear-resistant coating resin. The specific preparation steps are as follows: S1. Add 20 parts of mixed organic solvent to a dry mixing tank, then add 0.2 parts of dibutyltin dilaurate, 1 part of silane coupling agent KH-550 and 0.3 parts of antioxidant 264 in sequence, stir at 300 r / min for 15 min to obtain a premixed solution, and the whole process is under nitrogen protection. S2. Slowly add 40 parts of epoxy resin and 15 parts of polyhexamethylene adipate diol to the premixed liquid, stir at 600 r / min for 30 min, then add 5 parts of nano silica to the mixture while stirring, ultrasonically disperse at 300 W for 40 min and keep stirring at 500 r / min. S3. Under nitrogen protection, heat the mixed system to 60°C, slowly add 8 parts of diphenylmethane diisocyanate dropwise, and add it dropwise over 1 hour. Stir at 700 r / min, and after the dropwise addition is complete, keep the mixture at 70°C for 2 hours. S4. Cool the system to 50°C, add 3 parts of trimethylolpropane, and stir for 15 min. Slowly add a mixture of 10 parts of methyl methacrylate, 8 parts of butyl acrylate and 0.5 parts of benzoyl peroxide, and add it dropwise over 1 h. Simultaneously raise the temperature to 80°C and keep it at that temperature for 3 h. S5. Cool the system to 40℃, add 5 parts of dioctyl phthalate, and stir for 20 minutes; use a Fork-4 cup at 25℃ to test the viscosity and control it within 15 seconds; filter the coating through a 100-mesh dry nylon filter to obtain the cold-resistant and tear-resistant coating resin.
[0032] Example 2: Preparation of cold-resistant and tear-resistant coating resin. The specific preparation steps are as follows: S1. Add 35 parts of mixed organic solvent to a dry mixing tank, then add 0.8 parts of dibutyltin dilaurate, 3 parts of silane coupling agent KH-550 and 1 part of antioxidant 264 in sequence, stir at 500 r / min for 20 min to obtain a premixed solution, and the whole process is under nitrogen protection. S2. Slowly add 60 parts of epoxy resin and 25 parts of polyhexamethylene adipate diol to the premixed liquid, stir at 800 r / min for 40 min, then add 10 parts of nano silica to the mixture while stirring, ultrasonically disperse at 500 W for 60 min and keep stirring at 600 r / min. S3. Under nitrogen protection, heat the mixed system to 70°C, slowly add 15 parts of diphenylmethane diisocyanate dropwise over 1.5 hours, stirring at 900 r / min. After the addition is complete, keep the mixture at 80°C for 3 hours. S4. Cool the system to 60°C, add 8 parts of trimethylolpropane, and stir for 20 min. Slowly add a mixture of 20 parts of methyl methacrylate, 15 parts of butyl acrylate and 2 parts of benzoyl peroxide, and add it dropwise over 1.5 h. Simultaneously raise the temperature to 90°C and keep it at that temperature for 4 h. S5. Cool the system to 50℃, add 12 parts of dioctyl phthalate, and stir for 30 min; use a Fork-4 cup at 25℃ to test the viscosity and control it within 30 s; filter the coating through a 200-mesh dry nylon filter to obtain the cold-resistant and tear-resistant coating resin.
[0033] Example 3: Preparation of cold-resistant and tear-resistant coating resin. The specific preparation steps are as follows: S1. Add 27 parts of mixed organic solvent to a dry mixing tank, then add 0.5 parts of dibutyltin dilaurate, 2 parts of silane coupling agent KH-550 and 0.6 parts of antioxidant 264 in sequence, stir at 400 r / min for 17 min to obtain a premixed solution, and the whole process is under nitrogen protection. S2. Slowly add 50 parts of epoxy resin and 20 parts of polyhexamethylene adipate diol to the premixed liquid, stir at 700 r / min for 35 min, and then add 7 parts of nano silica to the mixing system while stirring, ultrasonically disperse at 400 W for 50 min and keep stirring at 550 r / min. S3. Under nitrogen protection, heat the mixed system to 65°C and slowly add 11 parts of diphenylmethane diisocyanate dropwise over 1.2 hours. Stir at 800 r / min and keep the mixture at 75°C for 2.5 hours after the addition is complete. S4. Cool the system to 55°C, add 5 parts of trimethylolpropane, and stir for 17 min. Slowly add a mixture of 15 parts of methyl methacrylate, 11 parts of butyl acrylate and 1 part of benzoyl peroxide, and add it dropwise over 1.2 h. Simultaneously raise the temperature to 85°C and keep it at that temperature for 3.5 h. S5. Cool the system to 45℃, add 8 parts of dioctyl phthalate, and stir for 25 minutes; use a Fork-4 cup at 25℃ to test the viscosity and control it within 20 seconds; filter the coating through a 150-mesh dry nylon filter to obtain the cold-resistant and tear-resistant coating resin.
[0034] Example 4: Preparation of modified epoxy resin. The specific preparation steps are as follows: A1. Add 400g of bisphenol A type epoxy resin to a dry four-necked flask, add 120ml of epichlorohydrin, stir and heat to 60℃, slowly add 80ml of 30% sodium hydroxide solution dropwise over 1.5h, and keep the reaction at 70℃ for 3h; after the reaction, add 80g of polyethylene glycol with a molecular weight of 1000, heat to 90℃, add 0.2g of boron trifluoride diethyl ether complex, stir and react for 4h; then cool to 50℃, wash twice with anhydrous ethanol, and remove ethanol and epichlorohydrin by vacuum distillation at 80℃ and -0.095MPa to obtain the first modified epoxy resin; A2. Take 300g of the first modified epoxy resin and add it to a dry four-necked flask. Add 100ml of xylene, stir and heat to 80℃. Then slowly add 60g of maleic anhydride and 1g of hydroquinone, heat to 110℃ and keep the temperature for 5h. Then cool down to 80℃, add 50g of silane coupling agent KH-560 and 0.2g of dibutyltin dilaurate, stir and react for 3h. Then remove xylene by vacuum distillation at 100℃ and -0.09MPa to obtain the second modified epoxy resin. A3. Take 200g of the second modified epoxy resin and add it to a dry four-necked flask. Add 80ml of N,N-dimethylformamide, stir and heat to 70℃, then add 30g of nano-calcium carbonate treated with silane coupling agent KH-550, and ultrasonically disperse for 30min. Then add 5g of benzoyl peroxide, heat to 90℃ and stir to react for 4h. After the reaction is completed, cool to room temperature, filter, and obtain the modified epoxy resin.
[0035] Example 5: Preparation of modified epoxy resin. The specific preparation steps are as follows: A1. Add 500g of bisphenol A type epoxy resin to a dry four-necked flask, add 150ml of epichlorohydrin, stir and heat to 70℃, slowly add 100ml of 30% sodium hydroxide solution dropwise over 2 hours, and keep the reaction at 80℃ for 4 hours; after the reaction, add 100g of polyethylene glycol with a molecular weight of 1000, heat to 100℃, add 0.5g of boron trifluoride diethyl ether complex, stir and react for 5 hours; then cool to 60℃, wash three times with anhydrous ethanol, and remove ethanol and epichlorohydrin by vacuum distillation at 80℃ and -0.095MPa to obtain the first modified epoxy resin; A2. Take 400g of the first modified epoxy resin and add it to a dry four-necked flask. Add 120ml of xylene, stir and heat to 90℃. Then slowly add 80g of maleic anhydride and 2g of hydroquinone, heat to 120℃ and keep the temperature for 6h. Then cool down to 90℃, add 70g of silane coupling agent KH-560 and 0.5g of dibutyltin dilaurate, stir and react for 4h. Then remove xylene by vacuum distillation at 100℃ and -0.09MPa to obtain the second modified epoxy resin. A3. Take 300g of the second modified epoxy resin and add it to a dry four-necked flask. Add 100ml of N,N-dimethylformamide, stir and heat to 80℃, then add 50g of nano-calcium carbonate treated with silane coupling agent KH-550, and ultrasonically disperse for 40min. Then add 8g of benzoyl peroxide, heat to 100℃ and stir to react for 5h. After the reaction is completed, cool to room temperature, filter, and obtain the modified epoxy resin.
[0036] Example 6: Preparation of modified nano-silica. The specific preparation steps are as follows: B1. Take 100g of nano silica and add 200ml of anhydrous ethanol. Disperse by ultrasonication for 20min. Then add 15ml of silane coupling agent KH-550. Adjust the pH to 4 with anhydrous acetic acid. Stir at 50℃ for 3h. After the reaction, centrifuge and wash with anhydrous ethanol 3 times. Dry under vacuum at 80℃ for 4h to obtain the first modified nano silica. B2. Add 80g of the first-modified nano-silica to a dry four-necked flask, add 150ml of anhydrous toluene, sonicate for 30min, then add 2g of dehydrated sorbitol monooleate and stir for 30min. Next, add dropwise a mixture of 30ml of methyl methacrylate and 20ml of butyl acrylate monomers, heat to 70℃, add 1g of azobisisobutyronitrile, and keep the reaction at this temperature for 4h. After the reaction is completed, cool to room temperature, centrifuge, wash three times with anhydrous ethanol, and vacuum dry at 80℃ for 5h to obtain the second-modified nano-silica. B3. Take 60g of the second modified nano-silica and add it to a dry four-necked flask. Add 120ml of toluene, stir and heat to 80℃, add 10g of propyltriethoxysilane isocyanate and 0.1g of dibutyltin dilaurate, and stir to react for 3h. After the reaction is completed, cool down to 60℃, add 8g of hydroxyl acrylic resin with a solid content of 50%, stir to react for 2h, and then remove the toluene by vacuum distillation at 90℃ and -0.09MPa to obtain modified nano-silica.
[0037] Example 7: Preparation of modified nano-silica. The specific preparation steps are as follows: B1. Take 150g of nano-silica and add 250ml of anhydrous ethanol. Disperse by ultrasonication for 30min, then add 20ml of silane coupling agent KH-550. Adjust the pH to 5 with anhydrous acetic acid and stir at 60℃ for 4h. After the reaction, centrifuge and wash with anhydrous ethanol 3 times. Dry under vacuum at 100℃ for 5h to obtain the first modified nano-silica. B2. Add 100g of the first-modified nano-silica to a dry four-necked flask, add 200ml of anhydrous toluene, sonicate for 40min, then add 3g of dehydrated sorbitol monooleate and stir for 30min. Next, add dropwise a mixture of 40ml of methyl methacrylate and 30ml of butyl acrylate monomers, heat to 80℃, add 2g of azobisisobutyronitrile, and keep warm for 5h. After the reaction is completed, cool to room temperature, centrifuge, wash 3 times with anhydrous ethanol, and vacuum dry at 100℃ for 6h to obtain the second-modified nano-silica. B3. Take 80g of the second modified nano-silica and add it to a dry four-necked flask. Add 150ml of toluene, stir and heat to 90℃, add 15g of propyltriethoxysilane isocyanate and 0.3g of dibutyltin dilaurate, and stir to react for 4h. After the reaction is completed, cool down to 70℃, add 12g of hydroxyl acrylic resin with a solid content of 50%, stir to react for 3h, and then remove the toluene by vacuum distillation at 90℃ and -0.09MPa to obtain modified nano-silica.
[0038] Comparative Example 1: A cold-resistant and tear-resistant coating resin was prepared. The specific preparation steps are as follows: The remaining steps remain unchanged, except that the epoxy resin in Example 3 is replaced with the modified epoxy resin prepared in Example 4 to prepare a cold-resistant and tear-resistant coating resin.
[0039] Comparative Example 2: A cold-resistant and tear-resistant coating resin was prepared. The specific preparation steps are as follows: The remaining steps remain unchanged, except that the nano-silica in Example 3 is replaced with the modified nano-silica prepared in Example 7 to prepare a cold-resistant and tear-resistant coating resin.
[0040] Comparative Example 3: A cold-resistant and tear-resistant coating resin was prepared. The specific preparation steps are as follows: The remaining steps remain unchanged, except that the epoxy resin in Example 3 is replaced with the modified epoxy resin prepared in Example 4, and the nano silica is replaced with the modified nano silica prepared in Example 7, to prepare a cold-resistant and tear-resistant coating resin.
[0041] Performance testing Test Project Test Standards Example 1 Example 2 Example 3 Comparative Example 1 Comparative Example 2 Comparative Example 3 Glass transition temperature Tg (°C) GB / T19466.2-2004 -18.5 -19.2 -20.1 -25.3 -24.8 -28.6 Tear resistance (kN / m) GB / T16578.1-2008 28.3 29.1 30.5 35.8 36.2 40.1 Adhesion (cross-cut test, grade) GB / T9286-2021 2 2 1 1 1 0 hardness GB / T6739-2022 HB HB H H H 2H Weather resistance (appearance changes after xenon lamp aging for 1000 hours) GB / T1865-2009 Slight loss of shine, with minor cracks appearing in some areas. Slight loss of shine, no obvious cracks Very slight loss of shine, no cracks No loss of gloss, no cracks No loss of gloss, no cracks No loss of gloss, no discoloration, no cracks, and virtually no change in appearance. Impact resistance (50cm, kg·cm) GB / T1732-2020 40 45 50 55 58 65 Elongation at break (%) GB / T1040.3-2006 18.2 20.5 22.8 28.5 29.3 33.6 Abrasion resistance (mg / 500r) GB / T1768-2006 8.5 7.8 7.2 6.1 5.8 4.5 Based on performance test data, regarding the glass transition temperature (Tg), the Tg values of Examples 1-3 ranged from -18.5℃ to -20.1℃, while Comparative Example 1 (using modified epoxy resin) had a Tg of -25.3℃, Comparative Example 2 (using modified nano-silica) had a Tg of -24.8℃, and Comparative Example 3 (using both) had a Tg of -28.6℃, demonstrating significantly better cold resistance. In terms of tear strength, Examples 1-3 ranged from 28.3 to 30.5 kN / m, while Comparative Examples 1, 2, and 3 showed a significant increase in strength due to the use of modified raw materials. Regarding adhesion, Examples 1-2 achieved a grade of 2, Example 3 a grade of 1, Comparative Examples 1-2 a grade of 1, and Comparative Example 3 a grade of 0, demonstrating superior adhesion. The strength gradually improved with the application of modified raw materials; in terms of hardness, Examples 1-2 were HB, Example 3 was H, Comparative Examples 1-2 were H, and Comparative Example 3 was 2H, showing an increasing trend in hardness; in terms of weather resistance, Example 1 had slight gloss loss and fine cracks, Example 2 had slight gloss loss but no obvious cracks, Example 3 had very slight gloss loss but no cracks, Comparative Examples 1-2 had no gloss loss or cracks, and Comparative Example 3 had basically no change in appearance, showing a gradual improvement in weather resistance; in terms of impact resistance (50cm, kg·cm), Examples 1-3 were 40-50, Comparative Examples 1-2 were 55-58, and Comparative Example 3 reached 65, showing a continuous improvement in impact resistance; the elongation at break and abrasion resistance were both better in the comparative examples. Overall, the coating resin using modified epoxy resin and modified nano-silica is superior to the resin without modified raw materials in terms of cold resistance, tear resistance, adhesion, hardness, weather resistance, and impact resistance, and the performance improvement is most significant when both are used together.
[0042] The above description is merely an example and illustration of the present invention. Those skilled in the art can make various modifications or additions to the specific embodiments described, or use similar methods to replace them, as long as they do not deviate from the invention or exceed the scope defined in the claims, all of which should fall within the protection scope of the present invention.
Claims
1. A cold-resistant and tear-resistant coating resin, characterized in that: It contains the following raw materials in parts by weight: 40-60 parts modified epoxy resin, 15-25 parts polyhexane adipate diol, 5-10 parts modified nano silica, 8-15 parts diphenylmethane diisocyanate, 3-8 parts trimethylolpropane, 10-20 parts methyl methacrylate, 8-15 parts butyl acrylate, 0.5-2 parts benzoyl peroxide, 0.2-0.8 parts dibutyltin dilaurate, 1-3 parts silane coupling agent KH-550, 0.3-1 part antioxidant 264, 5-12 parts dioctyl phthalate, and 20-35 parts mixed organic solvent.
2. The cold-resistant and tear-resistant coating resin according to claim 1, characterized in that: The mixed organic solvent consists of butanone, butyl acetate, and xylene in a ratio of 3:4:
3.
3. The cold-resistant and tear-resistant coating resin according to claim 1, characterized in that: The modified epoxy resin is prepared using the following specific steps: A1. Add bisphenol A type epoxy resin to a dry four-necked flask, add epichlorohydrin, stir and heat to 60-70℃, slowly add 30% sodium hydroxide solution dropwise over 1.5-2 hours, and keep the reaction at 70-80℃ for 3-4 hours; after the reaction, add polyethylene glycol with a molecular weight of 1000, heat to 90-100℃, add boron trifluoride diethyl ether complex, and stir for 4-5 hours; then cool to 50-60℃, wash 2-3 times with anhydrous ethanol, and remove ethanol and epichlorohydrin by vacuum distillation at 80℃ and -0.095MPa to obtain the first modified epoxy resin; A2. Take the first modified epoxy resin and add it to a dry four-necked flask. Add xylene, stir and heat to 80-90℃, then slowly add maleic anhydride and hydroquinone, heat to 110-120℃ and keep the temperature for 5-6 hours. Then cool down to 80-90℃, add silane coupling agent KH-560 and dibutyltin dilaurate, stir and react for 3-4 hours, and then remove xylene by vacuum distillation at 100℃ and -0.09MPa to obtain the second modified epoxy resin. A3. Take the second modified epoxy resin and add it to a dry four-necked flask. Add N,N-dimethylformamide, stir and heat to 70-80℃, then add nano-calcium carbonate treated with silane coupling agent KH-550, and ultrasonically disperse for 30-40 minutes. Then add benzoyl peroxide, heat to 90-100℃ and stir to react for 4-5 hours. After the reaction is completed, cool to room temperature, filter, and obtain the modified epoxy resin.
4. The cold-resistant and tear-resistant coating resin according to claim 3, characterized in that: The nano-calcium carbonate in A3 treated with silane coupling agent KH-550 is specifically treated as follows: 100g of nano-calcium carbonate is vacuum dried at 120℃ for 4h, 150ml of anhydrous ethanol is added and ultrasonically dispersed for 30min, then 10ml of silane coupling agent KH-550 is added, the pH is adjusted to 5 with anhydrous acetic acid, and the reaction is stirred at 60℃ and 500r / min for 3h. After the reaction is completed, the reaction solution is centrifuged, the precipitate is washed 3 times with anhydrous ethanol, and vacuum dried at 90℃ for 5h.
5. The cold-resistant and tear-resistant coating resin according to claim 3, characterized in that: The ratio of bisphenol A type epoxy resin, epichlorohydrin, sodium hydroxide solution, polyethylene glycol, and boron trifluoride diethyl ether complex in A1 is 400-500g: 120-150ml: 80-100ml: 80-100g: 0.2-0.5g; The ratio of the first modified epoxy resin, xylene, maleic anhydride, hydroquinone, silane coupling agent KH-560, and dibutyltin dilaurate in A2 is 300-400g: 100-120ml: 60-80g: 1-2g: 50-70g: 0.2-0.5g; The ratio of the second modified epoxy resin, N,N-dimethylformamide, nano-calcium carbonate treated with silane coupling agent KH-550, and benzoyl peroxide in A3 is 200-300g: 80-100ml: 30-50g: 5-8g.
6. The cold-resistant and tear-resistant coating resin according to claim 1, characterized in that: The modified nano-silica is prepared using the following specific steps: B1. Add nano-silica to anhydrous ethanol, sonicate for 20-30 min, then add silane coupling agent KH-550, adjust pH to 4-5 with anhydrous acetic acid, stir and react at 50-60℃ for 3-4 h; after the reaction, centrifuge, wash 3 times with anhydrous ethanol, and vacuum dry at 80-100℃ for 4-5 h to obtain the first modified nano-silica. B2. Add the first-modified nano-silica to a dry four-necked flask, add anhydrous toluene, and ultrasonically disperse for 30-40 min. Then add dehydrated sorbitol monooleate and stir for 30 min. Next, add a mixture of methyl methacrylate and butyl acrylate monomers dropwise. Heat to 70-80℃, add azobisisobutyronitrile, and keep the reaction at this temperature for 4-5 h. After the reaction is completed, cool to room temperature, centrifuge, wash three times with anhydrous ethanol, and vacuum dry at 80-100℃ for 5-6 h to obtain the second-modified nano-silica. B3. Take the second batch of modified nano-silica and add it to a dry four-necked flask. Add toluene, stir and heat to 80-90℃, add isocyanate propyltriethoxysilane and dibutyltin dilaurate, and stir to react for 3-4 hours. After the reaction is completed, cool down to 60-70℃, add 50% solid content hydroxyl acrylic resin, stir to react for 2-3 hours, and then remove toluene by vacuum distillation at 90℃ and -0.09MPa to obtain modified nano-silica.
7. The cold-resistant and tear-resistant coating resin according to claim 6, characterized in that: The ratio of nano-silica, anhydrous ethanol, and silane coupling agent KH-550 in B1 is 100-150g: 200-250ml: 15-20ml; The ratio of the first modified nano-silica, anhydrous toluene, dehydrated sorbitol monooleate, methyl methacrylate, butyl acrylate, and azobisisobutyronitrile in B2 is 80-100g: 150-200ml: 2-3g: 30-40ml: 20-30ml: 1-2g. The ratio of the amount of the second modified nano-silica, toluene, propyltriethoxysilane isocyanate, dibutyltin dilaurate, and hydroxyl acrylic resin in B3 is 60-80g: 120-150ml: 10-15g: 0.1-0.3g: 8-12g.
8. A method for preparing a cold-resistant and tear-resistant coating resin, characterized in that: Specifically, it includes the following steps: S1. Add the mixed organic solvent to the dry stirring tank, then add dibutyltin dilaurate, silane coupling agent KH-550 and antioxidant 264 in sequence, and stir at 300-500 r / min for 15-20 min to obtain the premixed solution. The entire process is under nitrogen protection to avoid oxidation of the raw materials and to provide a stable basic system for subsequent reactions. S2. Slowly add modified epoxy resin and polyhexanediol adipate to the premix, stir at 600-800 r / min for 30-40 min, then add modified nano silica to the mixture while stirring, ultrasonically disperse at 300-500 W for 40-60 min and keep stirring at 500-600 r / min to make the nanoparticles uniformly dispersed in the resin system and give full play to the reinforcing effect. S3. Under nitrogen protection, heat the mixed system to 60-70℃, slowly add diphenylmethane diisocyanate dropwise over 1-1.5 hours, stirring at 700-900 r / min. After the addition is complete, keep the mixture at 70-80℃ for 2-3 hours to ensure a full cross-linking reaction and the formation of a stable cross-linked network. S4. Cool the system to 50-60℃, add trimethylolpropane, and stir for 15-20 minutes; slowly add a mixture of methyl methacrylate, butyl acrylate and benzoyl peroxide, and add it dropwise over 1-1.5 hours. Simultaneously raise the temperature to 80-90℃ and keep it at that temperature for 3-4 hours to ensure complete copolymerization and form acrylate segments that have both hardness and flexibility. S5. Cool the system to 40-50℃, add dioctyl phthalate, and stir for 20-30 minutes; use a Fork-4 cup at 25℃ to test the viscosity and control it within 15-30 seconds; filter the coating through a 100-200 mesh dry nylon filter to avoid defects such as pinholes and particles on the coating surface, and obtain a cold-resistant and tear-resistant coating resin.
9. The method for preparing a cold-resistant and tear-resistant coating resin according to claim 8, characterized in that: All raw materials involved in the entire process of preparing modified epoxy resin, modified nano silica, and coating resin must be dried and dehydrated before being added to the reaction. The moisture content of the raw materials after treatment must be controlled below 0.1%. At the same time, the equipment used in the reaction must be dried in advance to ensure that the entire reaction system is in a low-water or anhydrous environment.
Citation Information
Cited By
High-toughness new energy automobile part bonding resin and preparation method thereof
CN121801537A